Combination of Nutritional Risk Index and Handgrip Strength on the Survival of Patients with Cancer Cachexia: A Multi- Center Cohort Study - Xie H; Ruan G; Zhang Q; Ge Y; Song M; Zhang X; Liu X; Lin S; Zhang X; Li X; Zhang K; Yang M; et al. (Dove Medical Press, 2022)
Hailun Xie,1- 3,* Guotian Ruan,1- 3,* Qi Zhang,1- 3,* Yizhong Ge,1- 3 Mengmeng Song,1- 3 Xi Zhang,1- 3 Xiaoyue Liu,1- 3 Shiqi Lin,1- 3 Xiaowei Zhang,1- 3 Xiangrui Li,1- 3 Kangping Zhang,1- 3 Ming Yang,1- 3 Meng Tang,1- 3 Minghua Cong,4 Hanping Shi1- 3 1Department of Gastrointestinal Surgery/Department of Clinical Nutrition, Beijing Shijitan Hospital, Capital Medical University, Beijing, 100038, People's Republic of China; 2Beijing International Science and Technology Cooperation Base for Cancer Metabolism and Nutrition, Beijing, 100038, People's Republic of China; 3Key Laboratory of Cancer FSMP for State Market Regulation, Beijing, 100038, People's Republic of China; 4Department of Comprehensive Oncology, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Hanping Shi, Department of Gastrointestinal Surgery/Department of Clinical Nutrition, Beijing Shijitan Hospital, Capital Medical University, Beijing, 100038, People's Republic of China, Email shihp@ccmu.edu.cnPurpose: The nutritional risk index (NRI) and handgrip strength (HGS) are useful indicators of nutritional and physical status, respectively, both of them can predict the prognosis of many cancers; however, the predictive accuracy of a single indicator is unsatisfactory. Whether the combination of NRI and HGS could enhance the stratification of the prognosis of patients with cancer cachexia.Patients and Methods: The study population was randomly divided into training and validation cohorts. We combined NRI and HGS and constructed the NRI-HGS score. Restricted cubic splines were used to assess the associations between NRI, HGS, and all-cause mortality. The Kaplan-Meier method was used to calculate the survival probability of the patients. The Cox proportional hazards risk model was used to analyze survival and prognostic factors.Results: Low NRI and low HGS were independent predictors of poor prognosis in patients with cancer cachexia. The NRI-HGS score showed a better prognostic stratification than either NRI or HGS. The co-occurrence of low NRI and low HGS was associated with an approximately 1.8-fold increased risk of mortality. The NRI-HGS score could effectively distinguish patients with a poor prognosis at different pathological stages. Furthermore, we constructed a novel prognostic nomogram based on NRI and HGS. The concordance index and calibration plot confirmed that the nomogram had good prognostic accuracy. The area under the receiver operating characteristic curve of the nomogram reached > 0.8, which was much higher than that of the traditional tumor-node-metastasis staging system. The nomogram provided better prognostic stratification for patients with cancer cachexia.Conclusion: Low NRI and low HGS are independent prognostic indicators in cancer cachexia. The combination of NRI and HGS improve prognostic stratification for patients with cancer cachexia. Our study suggests combining nutritional and physical status in future cachexia research.Keywords: nutritional risk index, handgrip strength, cancer cachexia, prognostic